Assessing systems thinking skills in two undergraduate sustainability courses: a comparison of teaching strategies - Hiller Connell, Kim Y.; Remington, Sonya M.; Armstrong, Cosette M. (My University, 2012)
The purpose of this study was to determine systems thinking skill development among undergraduate students and assess the effectiveness of two different instructional methods for increasing these skills. Undergraduate students from two four-year state institutions, one located in the Midwestern region (n=20) of the United States and one in the Southwestern region (n=16) participated in the study. To accomplish the research object, the study employed a mixed between-within subjects experiment. Employing two different systems thinking teaching interventions, one group of students was exposed to a one-time intervention while the other group was exposed to a more extended and holistic intervention. Data were collected at two points in time: pre- and post-intervention. At the beginning (pre-intervention) and end (postintervention) of one semester, students read case studies describing apparel firms’ sustainability efforts. The students were then tasked to identify sustainability challenges, analyze conflicts between challenges, and offer business recommendations. Using a rubric, the authors scored the students’ responses on a scale of 0 to 5 and assessed ability to 1) think holistically and 2)perceive interrelationships and resolve resulting conflicts. T-tests revealed that prior to the teaching interventions, as a whole, the students had unsophisticated skills related to their ability to think in systems. ANOVA revealed that, through instructional methods focused on systems thinking, it is possible to increase students’ ability to think in systems. Additionally, the study revealed that, compared to a constrained one-time intervention, a long-term, holistic, and integrated approach is significantly more effective in encouraging students’ system thinking competencies. Results of this study support the need for educators to integrate teaching methods designed to increase students’ systems thinking competencies holistically throughout course curriculum. Additionally, the study outlines a transferrable approach to assessing systems thinking skills within postsecondary education.
Keywords: Systems thinking; Assessment; Undergraduate; Sustainability education